2006
DOI: 10.1103/physrevb.73.165310
|View full text |Cite
|
Sign up to set email alerts
|

All-angle left-handed negative refraction in Kagomé and honeycomb lattice photonic crystals

Abstract: Possibilities of all-angle left-handed negative refraction in 2D honeycomb and Kagomé lattices made of dielectric rods in air are discussed for the refractive indices 3.1 and 3.6. In contrast to triangular lattice photonic crystals made of rods in air, both the honeycomb and Kagomé lattices show all-angle left-handed negative refraction in the case of the TM2 band for low normalized frequencies. Certain advantages of the honeycomb and Kagomé structures over the triangular lattice are emphasized. This specially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…These so-called photonic-bandgap fibers operate through bandgap effects of photonic crystals 11,12 , which occur because of periodic microstructuring of the dielectric in the cladding region. Photonic crystals have been studied extensively for their bandgap 1 and special in-band dispersion effects such as negative refraction 13 . However, another really interesting feature of photonic crystals is the Dirac points that appear at corners of the Brillouin zone [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…These so-called photonic-bandgap fibers operate through bandgap effects of photonic crystals 11,12 , which occur because of periodic microstructuring of the dielectric in the cladding region. Photonic crystals have been studied extensively for their bandgap 1 and special in-band dispersion effects such as negative refraction 13 . However, another really interesting feature of photonic crystals is the Dirac points that appear at corners of the Brillouin zone [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more complicated band structures appear. We demonstrated that both lattices (rods in air) had all-angle left-handed refraction for the TM2 band [16] where both effective indices, n peff (x, h i ) = sgn(v gr AE k PhC ) AE cjk PhC j/x = ±k PhC /k air and n beam (x, h i ) = sin(h i )/sin(h r ) (x, h i , and h r are the frequency, incident and, refracted angle, respectively) are close to À1. In Fig.…”
Section: Archimedean Lattice Photonic Crystalsmentioning
confidence: 95%
“…Earlier experimental and theoretical studies of the PCs have focused on photonic band gaps and several appropriate devices have already been developed [3]. But in the recent years, the studies have revealed that the photonic bands show unusual dispersion properties, which make them sources of several attractive effects [4,5] such as negative refraction and left handedness [6][7][8], super-prism [9], slow light [10] and SC [2,[11][12][13][14][15][16][17][18][19] effects. Among these, the SC in PCs provides a brand new way of confining light propagation, which is different from conventional PC waveguides.…”
Section: Introductionmentioning
confidence: 99%